(untitled) (Global Journal of Medical Research, 2024)
Central venous catheterization is a commonly performed procedure in operation theatre. After the advent of ultrasound (US)guided central venous catheterization (CVC), the incidence of life-threatening complications has reduced significantly and are rare. We present a case of haemothorax in a young patient after US guided which was inserted at the end of surgery under anaesthesia. The operator had some technical difficulty while inserting the CVC. The Haemothorax was diagnosed post-operatively in the ward after was missed clinically by radiological investigation. It was treated by inserting a 36 Fr chest drain on the second postoperative day which was removed on the seventh postoperative day and the patient was discharged to home.